KNOWLEDGE SHARING UNTUK MENINGKATKAN EFIKASI DIRI PROAKTIF DAN INOVATIF KARYAWAN PT. I - , MUHAMMAD KAMMAGAMA HARISMINA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Companies expect their employees to be more prepared and confident to be proactive and innovative. Proactive and innovative are not only to anticipate a change, but also engaged in creating positive change in the company. One of ways to make employee to be more prepared to be proactive and innovative is by providing knowledge sharing. Subjects in this study are eleven supervisory level employees were divided into an experimental group of six peoples and a control group of five peoples. This study uses the unrated quasi experimental control group design with pretest, posttest, and follow-up. The selection of subjects per group selected through discussions with the company. The result of this study is analyzed using the Mann Whitney test and interview. The result of analyze for proactive self efficacy at pretest demonstrate mean difference - 4.86 (p> 0.05). The increase of self efficacy proactive in posttest of experimental group is with a mean difference -0.63 (p> 0.05). At the follow up, the mean difference of two groups is 0.43 (p> 0.05). The result of analyze for innovative self efficacy at pretest demonstrate mean difference -20.20 (p> 0.05). The increase occurred during posttest with a mean difference -8.53 (p> 0.05). At the follow up, the mean difference of two groups is 0.13 (p> 0.05). The results of interview analysis concludes that knowledge sharing giving positive impact on team work, openness, communication patterns across division, an increase of self confidence in presenting ideas, innovation, also confidence of doing innovative and proactive. From the statistical analysis concluded that the hypotheses in this study which is knowledge sharing effective to increase self efficacy of innovative and proactive was not accepted.